Behavioral Foundations of Sustainability Transitions - Miklós Antal; Ardjan Gazheli; Jeroen van den Bergh (WWWforEurope, 2012)
"Writings on sustainability transitions generally do not say much about the particularities of the behavior of individuals and organizations. This is somewhat surprising since an important problem which transition management needs to tackle is inertia or resistance to change. Transition policy needs to account for the bounded rationality and social interaction of agents so as to arrive at a more realistic view of the limits and opportunities for realizing a transition. System failures like lock-in, unpredictability and surprise in innovation systems, and network interaction between agents have received some attention, but their behavioral underpinnings can be improved. The identification of relevant stakeholders in transition processes and their unique behavioral features is crucial for understanding how to stimulate transitions. In this paper we investigate opportunities to integrate various theories and disciplinary views on behavior into thinking about sustainability transitions with the aim to arrive at recommendations for more effective policies. For this purpose, we combine insights from the literatures on agency in sustainability transitions, on environmental policy under bounded rationality and social interactions, and on behavioral foundations of learning and innovation."
Keywords: D03; P28; P36; Q58; 330; Agency; behavioural economics; bounded rationality; innovation; learning; sustainability; transition